Twin Pregnancy with Hydatidiform Mole and Coexisting Fetus: Report of Three Cases and Review of Literature - Fariba Yarandi; Zahra Eftekhar; Narges Izadi-Mood; Zahra Elahi-Panah; Hadi Shojaei (Tehran University of Medical Sciences, 2009)
A twin pregnancy with a coexisting complete hydatidiform mole and a healthy fetus (CMCF) is rare. Here we report three cases of CMCF with different clinical courses but similar outcome without a surviving neonate. Two women required uterine evacuation before 20 weeks of gestational age because of vaginal bleeding and medical complications and the other patient underwent termination of her pregnancy at 24 weeks of gestation due to severe pre-eclampsia. The pathologic diagnosis of complete hydatidiform mole was confirmed in each case and the chromosome complement was 46XX in two molar gestations and 46XY in one gestation. One of the three women required chemotherapy for treatment of low-risk gestational trophoblastic disease. The hCG level was normalized after 4 cycles and the patient was free of disease at 1 year follow-up. Review of the literature discussing the diagnostic tools, clinical features, management and outcome of pregnancies with CMCF are presented.